The crustal structure of the western Himalayas and Tibet. Issue 5 (26th May 2015) - Gilligan, Amy; Priestley, Keith F.; Roecker, Steven W.; Levin, Vadim; Rai, S. S.
Abstract We present new, high‐resolution, shear velocity models for the western Himalayas and West Tibet from the joint inversion of P receiver functions recorded using seismic stations from four arrays in this region and fundamental mode Rayleigh wave group velocity maps from 5–70 s covering Central and Southern Asia. The Tibetan Plateau is a key locality in understanding large‐scale continental dynamics. A large number of investigations has examined the structure and processes in eastern Tibet; however, western Tibet remains relatively understudied. Previous studies in this region indicate that the western part of the Tibetan Plateau is not a simple extension of the eastern part. The areas covered by these arrays include the Karakoram and Altan‐Tagh faults, and major terrane boundaries in West Tibet and the Himalayas. The arrays used include broadband data collected by the West Tibet Array, a U.S.‐China deployment on the western side of the Tibetan Plateau between 2007 and 2011. We use the shear wave velocity models to obtain estimates of Moho depth. The Moho is deep (68–84 km) throughout West Tibet. We do not observe significant steps within the Moho beneath West Tibet. A large step in Moho depth is observed at the Altyn‐Tagh fault, where Moho depths are 20–30 km shallower to the north of the fault compared to those to the south. Beneath the Lhasa Terrane and Tethyan Himalayas, we observe a low‐velocity zone in the midcrust. This feature is not interrupted by the Karakoram Fault, suggesting that the Karakoram Fault does not cut through the entire crust.